THE ETHICAL CRISIS OF STUDENTS AND THE ROLE OF ‎THE QUR'AN, SUNNAH, AND IJTIHAD IN EDUCATION - Hidayat, Muhammad; Khadijah; Sari, Widya (International Journal of Multidisciplinary Reseach, 2025)
This article aims to analyze the growing ethical crisis among students in schools and Islamic boarding institutions and to examine the role of the Qur’an, Sunnah, and the principles of ijtihad in revitalizing fiqh learning to foster a dignified educational culture. This study employs a library research approach by reviewing classical and contemporary fiqh literature to explore the foundational concepts of Islamic law and their relevance for strengthening models, methods, strategies, media, and evaluation in fiqh instruction. The findings indicate that increasing cases of violence against teachers, bullying, harassment, and the cult of charismatic figures are closely related to the weak internalization of Islamic legal values in fiqh learning and the low level of students’ religious literacy. The discussion reveals that the normative values of the Qur’an and Sunnah offer a moral framework that can serve as the basis for designing effective fiqh learning, while ijtihad provides opportunities to develop contextual, critical, and responsive instructional approaches suited to contemporary educational challenges. These findings highlight the need to reconstruct integrative fiqh learning capable of reducing moral degradation and creating safe, humane, and civilized learning environments. The impact of this study lies in offering a Qur’an–Sunnah–Ijtihad–based framework for fiqh education as a comprehensive solution to current ethical problems among students.